2002
DOI: 10.1029/2002gl015744
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude pump‐induced optical emissions for frequencies close to the third electron gyro‐harmonic

Abstract: It has been long established that high‐power O‐mode HF pumping of the ionosphere can produce artificial optical emissions. 630 nm O(1D) photons are produced by pump‐accelerated electrons colliding with the F‐layer neutral oxygen. However, the mechanism for artificial electron acceleration remains unclear. Competing theories include Langmuir and upper‐hybrid turbulence. Pump‐induced HF coherent radar backscatter power is closely linked with upper‐hybrid turbulence, both of which are known to reduce when pumping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 31 publications
4
78
2
Order By: Relevance
“…Whilst the pump frequency does not appear important, pump power determines the electron temperature enhancement and plasma depletion depth in their model. However, we note that with a pump frequency of 2.85 MHz HAARP produces an O1D optical emission of 100 -300 R for 11 MW ERP Kosch et al, 2005], whereas for pump frequencies >4 MHz EISCAT produces O1D optical intensities of order 100 R for pump powers of 70-200 MW ERP [Kosch et al, 2000[Kosch et al, , 2002bRietveld et al, 2003]. Since the O1D 630 nm pumpinduced optical emission is at least partly a function of electron temperature [e.g., Ashrafi et al, 2006;Gustavsson et al, 2002], we conclude that low pump powers at HAARP are compensated by pumping the ionosphere near the second electron gyroharmonic, which seems to produce significant electron temperature enhancements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst the pump frequency does not appear important, pump power determines the electron temperature enhancement and plasma depletion depth in their model. However, we note that with a pump frequency of 2.85 MHz HAARP produces an O1D optical emission of 100 -300 R for 11 MW ERP Kosch et al, 2005], whereas for pump frequencies >4 MHz EISCAT produces O1D optical intensities of order 100 R for pump powers of 70-200 MW ERP [Kosch et al, 2000[Kosch et al, , 2002bRietveld et al, 2003]. Since the O1D 630 nm pumpinduced optical emission is at least partly a function of electron temperature [e.g., Ashrafi et al, 2006;Gustavsson et al, 2002], we conclude that low pump powers at HAARP are compensated by pumping the ionosphere near the second electron gyroharmonic, which seems to produce significant electron temperature enhancements.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Kodiak SuperDARN radar, which is sensitive to 10 m scale irregularities, did show natural background backscatter ($30 -35 dB), which was significantly enhanced by pumping ($50-60 dB) [Kosch et al, 2007] (not shown). Such natural backscatter at HAARP around sunset and pump-enhanced backscatter [e.g., Kosch et al, 2002b] are common. Obviously, the irregularities make for a nonideal reflecting surface and real flux density gain is most likely less than 30 dB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificially enhanced airglow due to excitation of oxygen atoms by accelerated electrons was also reported at Arecibo, Puerto Rico, by Gordon and Carlson [1974]. The electron acceleration is due to modified electron distributions by plasma waves such as Langmuir waves [Weinstock, 1975;Isham et al, 1999aIsham et al, , 1999b or UH resonance in the more recent study by Kosch et al [2002]. Optical observations were carried out with multiple wideand narrow-field systems at the HAARP site observing 557.7 and 630.0 nm emissions from atomic oxygen corresponding to >4.17 and >1.96 eV electron energy, respectively, and 427.8 nm N + 2 emissions indicating ionization production at >18 eV.…”
Section: Ion Gyro-features and Pump-induced Opticalmentioning
confidence: 89%
“…Coherent radar aspect angle variation and scintillation of satellite and radio source signals have been used in the past to study artificially-created field-aligned irregularities at a number of locations around the world (Frolov, 2003), but work on the aspect angle variation of electron temperature enhancements, Langmuir turbulence, RF-induced optical emissions, and stimulated electromagnetic emissions (SEE) has only relatively recently begun (Isham et al, 1999a, c;Kosch et al, 2000;Mishin et al, 2001;Pedersen et al, 2003;Rietveld et al, 2003;Frolov and Nedzvedski, 2004;Kosch et al, 2004;Frolov et al, submitted, 2004 1 Groves, private communication, 2003). The Sura facility (56.13 N latitude, 46.10 E longitude) transmits between 4.3 and 9.5 MHz with a maximum frequency-dependent ERP of between 80 and 280 MW, respectively (V. Frolov and E. Sergeev, private communications, 2003).…”
Section: Introduction and Summary Of Recent Aspect Angle Resultsmentioning
confidence: 99%